2015
DOI: 10.1007/s40268-015-0088-6
|View full text |Cite
|
Sign up to set email alerts
|

Budget Impact Analysis of Warfarin Reversal Therapies Among Hip Fracture Patients in Finland

Abstract: BackgroundHip fractures require operation within 36–48 h, and they are most common in the elderly. A high International Normalized Ratio should be corrected before surgery. In the current study, we analyzed the budget impact of various warfarin reversal approaches.MethodsFour reversal strategies were chosen for the budget impact analysis: the temporary withholding of warfarin, administration of vitamin K, fresh frozen plasma (FFP), and a four-factor prothrombin complex concentrate (PCC).ResultsWe estimated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This may allow surgery without major delay [ 10 ]. However, little is published in the literature on this topic and most of the authors who have studied the surgical management of patients on warfarin do not differentiate between different types of hip fractures or surgical methods [ 7 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may allow surgery without major delay [ 10 ]. However, little is published in the literature on this topic and most of the authors who have studied the surgical management of patients on warfarin do not differentiate between different types of hip fractures or surgical methods [ 7 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dose cessations or reductions are limited in terms of sensitivity, not appropriate for all patients, and may not offer the best cost–benefit balance owing to impacts on treatment effectiveness. Estimates from studies on warfarin reversal in hip replacement surgery have shown dose cessation to be the most expensive approach when direct costs arising during hospitalization are accounted for; 57 low-dose PCC has also been shown to be cost effective for management of VKA-induced bleeding versus a variable high-dose strategy. 58 However, a recent study suggests that management of dabigatran-associated major bleeding with dose cessation is as effective as or superior to drug withdrawal plus administration of red cell concentrates, plasma, or coagulation factor concentrates.…”
Section: Bleeding Management Strategies and Health Care Resource Usementioning
confidence: 99%
“…Different approaches for warfarin reversal in patients with hip fracture have been suggested [1,2,[5][6][7][8]10]. Available options include prothrombin complex concentrate (PCC), fresh frozen plasma (FFP), and vitamin K [7].…”
mentioning
confidence: 99%
“…As of today, there are no widely accepted guidelines for pharmacologic reversal of warfarin in patients requiring hip fracture surgery. Some authors suggested administration of vitamin K as a safe, effective, and cost-efficient method of reversing warfarin in patients undergoing hip fracture surgery [1,[5][6][7][8]. However, the ideal dosage, dosing schedule, and route of administration (oral versus subcutaneous or intravenous) remain unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation